Art as an Agent for Social Change - Pető, Áron (Central European Journal of Educational Research, 2025)
Bibliography of the reviewed book: Mreiwed, H., Carter, M. R. & Mitchell, C. (Eds.) (2021). Art as an Agent for Social Change. Brill Sense.